Performance based seismic analysis and design of suspension bridges. - Arzoumanidis, Serafim
This paper presents a performance-based seismic analysis and design of a large suspension bridge, the new Tacoma Narrows Parallel Crossing in the State of Washington. The scope of the project included establishment of design criteria, extensive analysis and validation of the design. The analysis was performed using detailed three-dimensional models that included geometric and material non-linearity. The target post-earthquake level of service was verified using stress, deformation and ductility criteria. In the absence of well-established criteria, which relate the structural response of tower shafts to specific levels of performance, capacity analyses were performed to demonstrate that the design fulfills the performance objectives. The seismic analysis and design of this bridge was reviewed throughout the design process. An independent check team also performed separate analysis and validation of the design. Thus, this bridge constitutes an example of a large scale design project where the performance based seismic design procedures underwent rigorous assessment. This work demonstrated that the performance based approach for seismic design is an appropriate way for designing earthquake resistant structures. Further data that relate the structural response with the performance objectives are necessary.
Keywords: Suspension bridges; Performance based seismic analysis and design; Caissons